DUSUN EMPELU DALAM KAJIAN BUDAYA 2010-2023 - Hadial Azizi; Zulfa; Juliandry Kurniawan Junaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses Empelu Hamlet in Cultural Studies from 2010 to 2023. The research questions are: How was Empelu Hamlet in cultural studies before 2010, and how did cultural traditions develop in Empelu Hamlet from 2010 to 2023? The objective of this study is to describe the development of cultural traditions in Empelu Village from 2010 to 2023 and before 2010. The research method used in this study is the Historical Research Method. This method consists of: 1) Heuristics, collecting data from archives, books, and documents, 2) Verification, testing the validity of the data, 3) Interpretation, analyzing the collected data, and 4) Historiography, compiling the research results into a report. The research results indicate that the development of cultural traditions in Empelu Village still preserves traditional customs, such as Baralek, Mandi Balasai, Balaie, Melebak, and Babantai, which still exist but appear sporadically in society. However, the influence of globalization and technological development has caused shifts in lifestyle patterns, particularly among the younger generation, who tend to abandon traditional cultural practices. Preservation efforts are carried out through traditional activities, local education, and local government support in the development of culture-based tourism. The conclusion of this study is that the culture of Empelu Hamlet remains intact despite undergoing changes, and a sustainable preservation strategy is needed to prevent it from losing its identity amid the tide of modernization.